(untitled) (Annals of Medical Research, 2021)
Aim: Our aim was to investigate the results of acupuncture in endovenous ablation treatment at 6–9 months.Materials and Methods: Group C (control,n=35) and Group A (acupuncture,n=35) patients included in this study were called by the cardiovascular surgeon for 6–9-month check-ups.Demographic characteristics, visual analogue scale (VAS) score,6–9 months saphenous vein diameter,patient satisfaction,CEAP classification, and other findings were recorded in both groups. Results: There was no difference between the groups in terms of age and body mass index.Patient satisfaction was higher in Group A (p=0.040).VAS scores were higher in Group C (p =0.002).There was an increase and a decrease in the saphenous vein diameter values of the patients at 6–9 months compared to the baseline values in Group C (p=0.004) and Group A (p=0.011),respectively.There was a decrease in the CEAP classification of the patients in Group C at 6–9 months compared to the baseline values (p=0,000).In Group A,there was a decrease in the CEAP classification of the patients at 6–9 months compared to the baseline values (p =0,000).In Group C,erythema 2 (5.7%),edema 7 (20.0%),and ıtching 7 (20.0%) were seen in the patients.In Group A, edema 3 (9.3%),itching 2 (5.8%),but not erythema were seen in the patients.In Group A, 34 of 35 patients stated their desire to recieve acupuncture again.Conclusion: Acupuncture increased patient satisfaction and reduced VAS scores and CEAP classification at 6–9 months.Acupuncture affected the saphenous vein diameters positively.There were less complications in the acupuncture group at 6–9 months.